The legend of The Jewish Entity in United States In Works of Abraham Regelson of the Narrative Collection “The House of the Spark” - ايمان لفته عزيز د. (lark, 2020)
Legends have been used as an explanatory method to illustrate human evolution and development. The legendary storytelling of Abraham Regelson in his story The Pillar of Gulls that appears in his collection Sparkle House implies that indigenous people in the United States are of Jewish descent. Its syntax and theme are similar to that of the texts of the book of Mormon and the Torah. It is a compensatory attempt to provide the Jewish immigrants with a sense of familiarity towards the place. In order to make a history for them there, he employs historical events already mentioned in the Book of Mormon. The religious myths are regarded as a psychological device that can achieve a great public impact. In fact, religious myths are considered sacred to the Jews. Thus, the story text uses a legendary romantic and aesthetic style where one resorts to the past to live with the present through legends.